Anionic Effect on Lanthanide(III) Metal Coordination Compounds of 4[N-(Benzalidene) Amino]Antipyrine Semicarbazone - Chakraborti, I.; Rai, H.C.; Goel, Neetu; Hashmi, N.M. (Asian Journal of Chemistry, 2010)
In the present work, the authors have studied the effect of chloro and perchlorato as anionic ligand on lanthanide(III) coordination compounds of 4[N-(benzalidene) amino] antipyrine semicarbazone. The isolated compounds have the composition LnCl3·2(BAAPS) and Ln(ClO4)3·2(BAAPS) (Ln = La, Pr, Nd, Sm, Gd, Tb, Dy or Ho). The compounds were characterized by elemental analysis, molar conductance, molecular weight, magnetic susceptibility, infra red and electronic spectra. The coordination number of central metal ion is either six or nine depending on the nature of anionic ligand. Thermal properties of the compounds were also studied.